Transparansi dan Akuntabilitas Sektor Publik: Pilar Utama dalam Good Governance - Kaila, Nazwa; Nawangsari, Ajeng (Universitas Prof.Hazairin,SH Bengkulu, 2025)
This study aims to analyze the role of transparency and accountability as key pillars in realizing good governance in the public sector. This study uses a qualitative descriptive approach with a Systematic Literature Review (SLR) method that examines various sources such as books, journals, and scientific articles from 2016 to 2024. Data was obtained through Google Scholar and SINTA using the keywords “Transparency,” “Accountability,” and “Good Governance.” The results show that transparency provides open access to information for the public, while accountability ensures that the government is responsible for its policies and budget use. These two aspects play an important role in improving the quality of governance, strengthening public trust, and encouraging public participation in policy oversight. This study is expected to provide input for policymakers to strengthen the implementation of the principles of transparency and accountability in order to create a more effective, open, and trustworthy government.